EVALUASI SOP (STANDARD OPERATING PROCEDURE) SEBAGAI PENUNJANG KINERJA PERUSAHAAN - Nugrahayanti, Andra Fyonaliza; Ikhtiara Kaideni Isharina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The objective of qualitative descriptive research is to evaluate the implementation of SOP in the internal affairs unit of PT XYZ. The data was gathered by conducting observations, documentation, triangulation, and interview with two internal affair officials of the company. Its validity was checked using credibility, transferability, dependability, and confirmability tests, and the analysis was conducted using the interactive model. The internal affairs unit has six SOPs; they are Post-Tenure Housing Allowances Payment, Integrated Building Maintenance, In- and Out-Office Meeting Facility Payment, Proposal Permit for Operational dan Positional Official Residence Placement, Provision of PT XYZ Guest House Facility, and Operational Vehicle Usage. The Result of the analyses indicate that the said unit has not fulfilled the seven principle for SOP arrangement. This makes the SOP fail in giving the maximum result. Other factors that hinder the implementation of the SOP is the weak regulation enforcement, frequent occurance of negotiation, and intervention of company leaders; all of which the standard cannot be applied properly. However, the SOP has helped the company attain its goals in terms of cost efficiency and maximum service.